2019
DOI: 10.1371/journal.pone.0214273
|View full text |Cite
|
Sign up to set email alerts
|

Fasting breath H2 and gut microbiota metabolic potential are associated with the response to a fermented milk product in irritable bowel syndrome

Abstract: Objectives Aim of this study was to assess the effect of a fermented milk product containing Bifidobacterium lactis CNCM I-2494 (FMP) on gastrointestinal (GI) symptoms and exhaled H 2 and CH 4 during a nutrient and lactulose challenge in patients with irritable bowel syndrome (IBS). Methods We included 125 patients with IBS (Rome III). Fasted subjects were served a 400ml liquid test meal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(35 citation statements)
references
References 49 publications
3
31
1
Order By: Relevance
“…Interestingly, we found that patients with severe IBS symptoms had a higher abundance of hydrogenases involved in the metabolism of H 2 . This is in agreement with our previous finding that IBS patients with high exhaled H 2 levels had a distinctive ratio of active members of the gut microbiota regardless of gastrointestinal symptoms 37 . We confirm the important role of hydrogen metabolism and provide novel insight into the identification of specific hydrogenases for symptom generation in IBS.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, we found that patients with severe IBS symptoms had a higher abundance of hydrogenases involved in the metabolism of H 2 . This is in agreement with our previous finding that IBS patients with high exhaled H 2 levels had a distinctive ratio of active members of the gut microbiota regardless of gastrointestinal symptoms 37 . We confirm the important role of hydrogen metabolism and provide novel insight into the identification of specific hydrogenases for symptom generation in IBS.…”
Section: Discussionsupporting
confidence: 93%
“…A 15-day period in the run-in phase was allowed before the flatulogenic diet to avoid potential carry-over effects of probiotic consumption in the habitual diet of the participants prior to their inclusion in the study. During the study, participants consumed their habitual diet except during the last 3 days of the run-in phase (days [16][17][18] and the administration phase (days 44-46) when a flatulogenic diet (see below) was administered. The day after the run-in phase (day 19) subjects were re-evaluated, and only subjects who fulfilled the 2 following continuation criteria entered the administration phase: (a) ≥50% daily compliance to the flatulogenic diet (calculated as the percent intake per day of the total fiber content in the diet); and (b) an increase in flatulence score ≥2 on a 0-10 scale during the flatulogenic diet as compared to the habitual diet.…”
Section: Methodsmentioning
confidence: 99%
“…The challenge diet [22] consisted of: (a) breakfast of wholemeal cookies (39 g) plus coffee, tea, and/or milk; (b) lunch of white beans (200 g), mixed vegetables (250 g) or chickpeas (200 g) and wholemeal bread (50 g), plus meat, fowl or fish, and fruit (banana, figs, peaches or prunes); and (c) dinner of vegetable soup (200 mL), wholemeal bread (50 g) and fruit (banana, figs, peaches, or During the study, participants consumed their habitual diet except during the last 3 days of the run-in phase (days [16][17][18] and the administration phase (days 44-46) when a flatulogenic diet (see below) was administered. The day after the run-in phase (day 19) subjects were re-evaluated, and only subjects who fulfilled the 2 following continuation criteria entered the administration phase: (a) ≥50% daily compliance to the flatulogenic diet (calculated as the percent intake per day of the total fiber content in the diet); and (b) an increase in flatulence score ≥2 on a 0-10 scale during the flatulogenic diet as compared to the habitual diet.…”
Section: Challenge Dietmentioning
confidence: 99%
See 2 more Smart Citations